2020
DOI: 10.3892/ol.2020.12414
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prognostic nutritional index predicts short‑ and long‑term outcomes after liver resection in patients with hepatocellular carcinoma

Abstract: The prognostic nutritional index (PNI) is one of the immune parameters calculated on the basis of the serum albumin and the total lymphocyte count. The aim of the present study was to investigate the prognostic significance of the PNI for short-and long-term outcomes after liver resection for patients with hepatocellular carcinoma (HCC). Data from 162 surgically treated patients with HCC (without any previous treatment) were retrospectively analyzed. The cutoff value of preoperative PNI was 45.0, which was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…The PNI was initially designed to assess the risk of surgical complications and mortality in patients undergoing gastrointestinal tract surgery (22). Increasing studies suggested that preoperative PNI could predict the overall survival of HCC patients undergoing surgery or targeted therapy (9,10,23). Our study is somewhat different from previous studies.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The PNI was initially designed to assess the risk of surgical complications and mortality in patients undergoing gastrointestinal tract surgery (22). Increasing studies suggested that preoperative PNI could predict the overall survival of HCC patients undergoing surgery or targeted therapy (9,10,23). Our study is somewhat different from previous studies.…”
Section: Discussioncontrasting
confidence: 84%
“…Furthermore, it is reported that the presence of an inflammatory response is pathogenic in the development of cancer-associated malnutrition, especially in patients with cirrhosis (5). The prognostic nutritional index (PNI), an overall measure of a patient's immunonutritional condition, has been demonstrated to be an independent prognostic factor in various types of cancer, such as gastric carcinoma (6), colon cancer (7), pancreatic cancer (8), and HCC (9,10). The previous studies have been reported that the PNI was a prognostic factor for evaluating short-and long-term outcomes after liver resection in HCC patients (9) and preoperative PNI predicts prognosis after curative hepatectomy in early Barcelona clinic liver cancer (BCLC) stage HCC (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Recently, there is growing evidence in HCC patients that PNI correlates with prognosis following non-surgical treatment and liver resection. [14][15][16] Its predictive significance in the LT setting remained, however, so far undetermined. Therefore, we conducted a retrospective study to explore the prognostic impact of preoperative PNI in HCC patients following LT.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin-bilirubin (ALBI) was first attempted to assess the liver function reserve of patients diagnosed with hepatocellular carcinoma (HCC) the same as the Child-Pugh grade in 2015, but ALBI had better predictive ability than the Child-Pugh grade for postoperative liver failure and long-term survival of patients undergoing liver resection (7,8). Several recent studies have demonstrated that the PNI and ALBI are closely related to the prognosis of patients with HCC, ICC, and gallbladder cancer (8)(9)(10)(11)(12)(13). Both the preoperative nutritional status and the immunological status have been reported to be independent prognostic factors of patients with ICC (11,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%